On the Simon-Spencer Theorem - Gordon, A.; Holt, J.; Laptev, A.; Molchanov, S. (Журнал математической физики, анализа, геометрии, 2008)
This paper presents a generalization of the classical result by B. Simon and T. Spencer on the absence of absolutely continuous spectrum for the continuous one-dimensional Schr odinger operator with an unbounded potential.